2017
DOI: 10.5005/jp-journals-10057-0050
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Prevalence and Antibiotic Susceptibility Pattern of Acinetobacter baumannii in Clinical Samples obtained from Patients admitted in Various Wards and Intensive Care Units

Abstract: Introduction: Acinetobacter baumannii is a nonfermentative and nonmotile, Gram-negative coccobacillus, which is the most often identified pathogen among Acinetobacter species that causes wide range of infection in humans. It has emerged as one of the most troublesome pathogens for health care institutions globally. Acinetobacter baumannii strains resistant [multidrug-resistant A. baumannii (MDR-Ab)] to all known antibiotics have now been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…However, the subsequent data from 12 European countries18 revealed a significant increase in the resistance rates against imipenem (42.5%) and meropenem (43.4%) [25].Data of the antibiotic susceptibilities from different geographical regions revealed that the resistance of Acinetobacter spp. to imipenem was in the range of, no resistance to 40% (2000-2004) [26].Other studies have also reported increasing resistance to carbapenems [9,23],which is reflected in our study as well.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…However, the subsequent data from 12 European countries18 revealed a significant increase in the resistance rates against imipenem (42.5%) and meropenem (43.4%) [25].Data of the antibiotic susceptibilities from different geographical regions revealed that the resistance of Acinetobacter spp. to imipenem was in the range of, no resistance to 40% (2000-2004) [26].Other studies have also reported increasing resistance to carbapenems [9,23],which is reflected in our study as well.…”
Section: Resultssupporting
confidence: 86%
“…Gender ratio was 1.9:1, which shows a female preponderance in our study. This was not the case with most studies that reported a slight male preponderance [7][8][9]. Saha et al and Sivaranjaniet al [11,12] have reported slight predominance of female patients over male.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…There was no gender-based difference in the frequency of isolation of A. baumannii in the current study, which is in contrast with the findings of previous studies showing a higher frequency of isolation among males. [ 14 15 ] Medical and surgical interventions such as urinary and central venous catheterization, mechanical ventilation, prior surgery, etc., are potential risk factors associated with A. baumannii infection. [ 16 17 ] In the current study, the majority of the patients had been exposed to one or more of these interventions either in the wards or ICUs.…”
Section: Discussionmentioning
confidence: 99%